Increased salt consumption induces body water conservation and decreases fluid intake - Rakova, Natalia; Kitada, Kento; Lerchl, Kathrin; Dahlmann, Anke; Birukov, Anna; Daub, Steffen; Kopp, Christoph; Pedchenko, Tetyana; Zhang, Yahua; Beck, Luis; Johannes, Bernd; Marton, Adriana; et al. (Journal of Clinical Investigation, 2017)
BACKGROUND: The idea that increasing salt intake increases drinking and urine volume is widely accepted. We tested the hypothesis that an increase in salt intake of 6 g/d would change fluid balance in men living under ultra-long-term controlled conditions. METHODS: Over the course of 2 separate space flight simulation studies of 105 and 205 days' duration, we exposed 10 healthy men to 3 salt intake levels (12, 9, or 6 g/d). All other nutrients were maintained constant. We studied the effect of salt-driven changes in mineralocorticoid and glucocorticoid urinary excretion on day-to-day osmolyte and water balance. RESULTS: A 6-g/d increase in salt intake increased urine osmolyte excretion, but reduced free-water clearance, indicating endogenous free water accrual by urine concentration. The resulting endogenous water surplus reduced fluid intake at the 12-g/d salt intake level. Across all 3 levels of salt intake, half-weekly and weekly rhythmical mineralocorticoid release promoted free water reabsorption via the renal concentration mechanism. Mineralocorticoid-coupled increases in free water reabsorption were counterbalanced by rhythmical glucocorticoid release, with excretion of endogenous osmolyte and water surplus by relative urine dilution. A 6-g/d increase in salt intake decreased the level of rhythmical mineralocorticoid release and elevated rhythmical glucocorticoid release. The projected effect of salt-driven hormone rhythm modulation corresponded well with the measured decrease in water intake and an increase in urine volume with surplus osmolyte excretion. CONCLUSION: Humans regulate osmolyte and water balance by rhythmical mineralocorticoid and glucocorticoid release, endogenous accrual of surplus body water, and precise surplus excretion. FUNDING: Federal Ministry for Economics and Technology/DLR; the Interdisciplinary Centre for Clinical Research; the NIH; the American Heart Association (AHA); the Renal Research Institute; and the TOYOBO Biotechnology Foundation. Food products were donated by APETITO, Coppenrath und Wiese, ENERVIT, HIPP, Katadyn, Kellogg, Molda, and Unilever.
EVALuna2:34240